An Evaluation Of Scale Efficiency Of Local Commercial Banks In Malaysia - RM. AN Annamalai, Veerappan (2000)
This study is basically motivated by the current spate of bank mergers both at home and abroad. The rationale for this consolidation excercise is that the larger banks would be better able to serve its customers as a result of economies of scale. Thus, this study investigates the scale efficiency among local commercial banks in Malaysia.